Relationships between training load, salivary cortisol responses and performance during season training in middle and long distance runners - Balsalobre-Fernandez, C.; Tejero-Gonzalez, C. M.; del Campo-Vecino, J. (PLOS ONE, 2014)
Purpose: Monitoring training from a multifactorial point of view is of great importance in elite endurance athletes. This study aims to analyze the relationships between indicators of training load, hormonal status and neuromuscular performance, and to compare these values with competition performance, in elite middle and long-distance runners. Method: Fifteen elite middle and long-distance runners (12 men, 3 women; age = 26.3±5.1 yrs) were measured for training volume, training zone and session rate of perceived exertion (RPE) (daily), countermovement jump (CMJ) and salivary free cortisol (weekly) for 39 weeks (i.e., the whole season). Competition performance was also observed throughout the study, registering the season best and worst competitions. Results: Season average salivary free cortisol concentrations correlate significantly with CMJ (r = -0.777) and RPE (r = 0.551). Also, weekly averages of CMJ significantly correlates with RPE (r = -0.426), distance run (r = -0.593, p<0.001) and training zone (r = 0.437, p<0.05). Finally, it was found that the CMJ (+8.5%, g = 0.65) and the RPE (-17.6%, g = 0.94) measured the week before the best competition performance of the season were significantly different compared with the measurement conducted the week before the season`s worst competition performance. Conclusions: Monitoring weekly measurements of CMJ and RPE could be recommended to control training process of such athletes in a non-invasive, field-based, systematic way.